The Effectiveness of the PrimaKu Application on Parents Behavior in Monitoring the Growth of Toddlers - Sahariah Sahariah; Nyimas Heny Purwati; Anita Apriliawati (UIMA Press, 2023)
Background: Child development is an important factor. The success of each phase affects the child's ability in the next phase. The low level of knowledge, attitudes and actions of parents about growth, and development disorders can cause deviations in growth, development, and mental and emotional disorders. Objectives: This study aims to determine the effectiveness of the PrimaKu application on the behavior (knowledge, attitudes, and actions) of parents in monitoring the growth and development of toddlers in the Panincong Health Center Work Area, Soppeng Regency. Methods: The research design used a quasi-experimental design with a nonequivalent control group pre and post-test design. The sample consisted of 36 respondents who were divided into the intervention and control groups. Data were analyzed using T-test. Results: The results showed that there was an effect of the PrimaKu application on the knowledge (p-value = 0.0001), attitudes (p-value = 0.0001) and actions (p value = 0.0001) of parents in monitoring the growth and development of toddlers, there was an average difference knowledge (p-value = 0.007 ), attitudes (p-value = 0.007) and actions (p-value = 0.028) of parents in the intervention group and control group (p-value = 0.0001). Conclusion: Parents should be able to use the PrimaKu application to improve behavior (knowledge, attitudes, and actions) in monitoring the growth and development of toddlers.